Three shades of `urban-digital citizenship': borders, speculation, and logistics in Cape Town - Ilia Antenucci; Federico Tomasello (Citizenship Studies, 2022)
Drawing upon case studies from Cape Town, `Africa's smartest city', this article proposes three theses on `urban-digital citizenship'. First, we suggest that urban-digital citizenship is defined by borders which operate: i) at a socio-spatial level, through the unequal distribution of digital infrastructures across the urban space; ii) through the algorithmic techniques of monitoring, profiling, and sorting, which filter access to urban services, mobility, and participation. Our second argument is that urban-digital citizenship is `speculative'. The algorithmic infrastructures that have increasingly come to govern urban life operate according to logics of preemption and experimentation that seek to model, and act upon, an array of possible future scenarios. The digitalisation of emergency and security response in Cape Town offers powerful examples of the ways in which urban citizens are caught in a mechanism of machine-learning speculations on future risks and anticipatory interventions. Finally, we propose that digital citizenship has a logistical character. Increasingly, `smart' cities such as Cape Town function as clusters in global circuits of data, technology, and finance. As data centres and tech startups are concentrated in the urban area, urban citizens have become a testbed for new technological products and a crucial node in the geography of cloud computing.
Keywords: 320; algorithmic governance; digital citizenship; intra-urban borders; smart cities; urban citizenship